Advocacy religious speech in the Algerian written press. A case analytical study of echorouk daily newspaper numbers - Neche, Azouz (Journal of Social Sciences and Humanities, 2021)
This study comes in order to shed light on the Advocacy of religious speech in the Algerian written press, specifically through the echorouk daily newspaper numbers. by the writer, Soltani Broken as a model advocacy religious content writer addressed to the readers in the favour of the Islamic Advocacy (Da'wa). As the study seeks to reveal the trends of the Advocacy religious essay, and the most important topics that focus on it, and the methods used in convincing. This study is classified as an analytical descriptive study, where a content analysis tool was used for a total of 37 articles, which were written by Soltani broken, during the holy month of Ramadan. The study concluded in its advocacy topic, in touching on various religious issues that are concerned with the Islamic nation (Ummah), where subjects of worshipping, occupied the first rank in the field of other subjects, then followed by doctrinaire and behavioral topics. The study also showed the necessity of taking advantage of the holy month of Ramadan, in penance, obedience and prayer as a real goal.